INVESTIGATION ON THE CYTOTOXIC NATURE OF LEAF AND STEM BARK EXTRACTS OF PROSOPIS CINERARIA - Robertson, Stellaa; Narayanan, N; Ravichandran, V (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: To investigate the cytotoxic activity of hydroalcoholic extracts of leaf and Stem bark of Prosopis cineraria using two human cancer cell lines such as HeLa and MCF-7. Methods: The cytotoxic activity was evaluated by trypan blue exclusion and MTT assay. The apoptosis influencing activity of extracts in cancer cell lines were performed using Hoechst staining technique. Results: Among the tested cell lines, Leaf extracts was more selective cytotoxic against HeLa and MCF-7 cell line than Stem bark extracts. In apoptotic study, morphological changes induced in HeLa and MCF-7 cells by both extracts were evidenced by using Hoechst staining and fluorescent microscopy. It was observed that there is marked increase in the number of MCF-7 and HeLa cells with the typical features of apoptosis, consisting in cells with condensed and fragmented nuclei. Conclusion: The present study proves the traditional claim of the plant in the management of cancer. Keywords: Prosopis cineraria, 3-(4, 5-dimethylthiazol-2yl)-2, 5-diphenyltetrazoliumbromide, Apoptosis, Cytotoxic activity, Leaf, Stem bark.